PEMANFAATAN SEDIMEN SELOKAN SALURAN AIR DI DINOYO SURABAYA SEBAGAI CAMPURAN MEDIA TANAM GUNA MENDUKUNG URBAN FARMING YANG RAMAH LINGKUNGAN - Firra Rosariawari; Fabian Pascalis Serenai (EnviroUS, 2022)
Dredging sediment by the Public Works Department of Highways and drainage Surabaya generate sediments as much as 595 040 m3 / year. Sediment reuse is intended to increase the potential value of sediment as a nursery growing medium for landscaping or urban agriculture, this study aims to determine the effect of sediment as a planting medium by mixing the results of other waste processing, including green compost and coco peat using variations 1:1;1, 1:3:1, 1:5:1, the vegetative test of Capsicum frutescens nursery for 2 weeks, and response to the addition of NPK fertilizer. The results of the study after pretreatment drying, pulverizing, sifting showed the best mixture ratio was 1; 1; 1 with the final result parameters C 3.58%, N 0.31%, P 0.02%, K 1.63%, CEC 43 .92 emol/kg, C/N 21, pH 8.55, no toxicity with percentage inhibition of seed growth 4%, optimal nursery growth and lower nutrient loss. Research shows that sediment can be used as a mixed substrate for eco-friendly planting media in sustainable long time.